Why People Emigrate to Work in Elder Care? - Rapolienė, Gražina; Ayalon, Liat (Socialinė teorija, empirija, politika ir praktika, 2021)
Emigration is one of the sorest problems in Lithuania. Emigrants from Lithuania most often fill the sector of unskilled labour in the target countries, one of which is elder care. Financial factors are considered the main motivation for emigration; however, migration is a complex phenomenon and requires a more nuanced investigation. The aim of this article is to analyse subjectively identified reasons of emigration from Lithuania to work in the elder care sector and motivation in choosing a particular country. The thematic data analysis of 13 semi-structured interviews revealed that emigration is motivated by an entirety of reasons: beside financial factors other „push“ (family, health) and „pull“ (knowledge about the country, family formation) factors are important. The move also is facilitated by the chain migration factors. The importance of the economic reasons for migration is revealed in cases of financial insecurity (loss of employment, threat of company bankruptcy, financial difficulties in the parents’ family etc.). Economic considerations become significant again, when comparing the job options and working conditions available to migrants. Work in the care sector for older people is seen as relatively easy, accessible and well paid. Other “push” factors were related to an unsatisfactory life situation, including stressful employment, and unsatisfying family relationships. The desire to get to know a foreign country, the opportunity to start a family or establish oneself there can work as „pull“ factors. The decision to emigrate was supported by the chain migration factors – encouragement, help and support of previously established immigrants. In some cases, it emerged as an independent factor of migration people emigrated, invited by relatives or acquaintances from abroad even though they did not initially plan to migrate. With the rapidly growing share of older people in Lithuania and the underdeveloped care services, the opportunity to retain potential emigrants by creating attractive working conditions for them in Lithuania, remains untapped. Policies should aim to improve the working conditions and opportunities in the care sector in Lithuania in order to encourage Lithuanians to stay in the country. In addition, regulations to better absorb (returning) migrants should be in place, given the ongoing movement between countries.